Roles of Administrators in Enhancing Teaching and Learning in Ilorin South Local Government Public Secondary Schools (Kwasu International Journal of Educational Management and Leadership, 2026)
The roles of school administrators towards enhancing effective teaching and learning cannot be overemphasized. Thus, the study examines the roles of administrators of public secondary schools in enhancing teaching and learning in Ilorin south local government public secondary schools, Kwara State. The paper examines the concept of school administrators and take into cognizance the qualities and roles of school administrators consecutively. The importance of school administration in teaching and learning as well as the challenges facing school administrators towards enhancing effective teaching and learning were also taken into cognizance while the strategies for enhancing school administration was not left out in the discussion. The study suggested among other that capacity building should be periodically organized for administrators of schools to enhance the efficacy of teaching and learning in the school system.